PROPORTIONAL ARMAMENT MODEL AND ITS ANALYSIS ON TIME SCALES - Ozdemir, Zehra; Yilmaz, Emrah (Amer Inst Mathematical Sciences-Aims, 2025)
In this study, it is underlined that countries engage in arms production and allocate expenditures for this purpose of ensuring their security. This study focuses on a model representing countries' armament expenditures, which will be solved and analyzed both in classical case and on proportional time scales. By presenting insights into defense expenditures, our study aims to analyze countries' attitudes toward one another. Proportional Laplace transform on time scales will be employed to solve the proportional armament model.
Keywords: Time scales; proportional derivative; armament model